2020
DOI: 10.1002/bies.201900219
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Autotomy and CNS Regeneration: Echinoderms as Non‐Model Species for Regenerative Biology

Abstract: Achieving regeneration of the central nervous system (CNS) is a major challenge for regenerative medicine. The inability of mammals to regrow a severed CNS contrasts with the amazing regenerative powers of their deuterostome kin, the echinoderms. Rapid CNS regeneration from a specialized autotomy plane in echinoderms presents a highly tractable and suitable non‐model system for regenerative biology and evolution. Starfish arm autotomy triggers mass cell migration and local proliferation, facilitating rapid CNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…The most common cause seems to be by regeneration process (Hotchkiss, 1979). Incidence of mutilation in some starfish has been suggested by fishing gears (Ramsay et al, 2001;Byrne, 2020). It is not considered in this study because the population studied was located inside a protected area where fishing activities are not allowed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cause seems to be by regeneration process (Hotchkiss, 1979). Incidence of mutilation in some starfish has been suggested by fishing gears (Ramsay et al, 2001;Byrne, 2020). It is not considered in this study because the population studied was located inside a protected area where fishing activities are not allowed.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration is a common phenomenon in all actual echinoderm classes (Yousra et al, 2018;Byrne, 2020). It has been particularly well-studied in asteroids, where three main aspects have been identified: 1) regeneration of body parts (arms) following self-induced or traumatic amputation; 2) regeneration of internal organs (pyloric caeca and cardiac stomach) following self-induced or traumatic mutilation, and 3) fission processes (Candia-Carnevali, 2006).…”
mentioning
confidence: 99%
“…In some studies of arm regeneration in brittle stars and starfish, clustered undifferentiated cells in regenerating arm tips were recognized by detailed microscopic observations including TEM, and those growth buds are referred as “blastema” (e.g., Biressi et al, 2010; Byrne, 2020). On the other hand, our study focused on the regenerative (and branching) process of arms of Astrocladus dofleini , and did not confirm that the cells clustered at the regenerating arm tip was undifferentiated.…”
Section: Discussionmentioning
confidence: 99%
“…Byrne et al (2019) induced autotomy of arms in Coscinasterias muricate , observed the regeneration process, especially focusing on cellular behavior in the tissue by immunostaining (e.g., increased glial cells). This study also insisted that the induction of autotomy, rather than artificial arm amputation, is important for observing natural arm regeneration process (Byrne, 2020; Byrne et al, 2019; Wilkie, 1978, 2001). In sea feathers (Crinoidea), Shibata, Oji, Akasaka, and Agata (2010) described the histological process of arm regeneration and subdivided it into nine phases, which were similar to those of ophiuroids.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation